Experimental Apparatus for Roll-Wave Measurements and Comparison with a 1D Mathematical Model - Maciel, G. F. [UNESP]; Ferreira, F. O. [UNESP]; Cunha, E. F. [UNESP]; Fiorot, G. H. [UNESP] (Asce-amer Soc Civil Engineers, 2017)
An experimental approach to examine the instabilities present on free surfaces of non-Newtonian fluid flow occurring in inclined channels is presented. When these flows occur in favorable conditions of inclination and discharge, it is observed that the propagation of instabilities can evolve into a specific type of wave, known as roll waves. The experimental apparatus developed allows simulation of stabilized roll waves in many scenarios for Newtonian and non-Newtonian rheology fluids, thereby constituting a highly useful approach for the understanding and control of roll waves. The fluid test for the non-Newtonian case used a gel rheometrically representative of the muddy material presented in natural disasters, such as mudflows. A low-cost, high-performance, and nonintrusive level measurement system (ultrasonic transducer) is proposed. A comparison between the experimental results obtained and a one-dimensional (1D) mathematical model exhibited good amplitude and wave-period estimations.
Keywords: Roll waves; Low-cost experimental apparatus; Non-Newtonian fluids; Ultrasonic transducer